KESANTUNAN TUTURAN IMPERATIF RAJA PARHATA PADA PESTA PERNIKAHAN ADAT BATAK TOBA - Togatorop, Irma S; Burhanudin, Dudung; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is titled politeness of imperative speech of raja parhata at traditional Batak Toba wedding party. This study aims to describe the form of imperative speech that is used raja parhata at Batak Toba wedding party. This research type is qualitative research by using descriptive method. Sources of research data is a traditional wedding party Batak Toba. The data of this research is imperative speech of raja parhata at traditional Batak Toba wedding party. Data collection techniques used in this research are recording techniques, gather techniques, and note techniques. Then the data is analyzed by classifying the data that has been obtained into the language unit containing imperative speech. Further describes imperative courtesy based on imperative speech, describes markers of imperative politeness, and summarizes data that has been analyzed. Based on the data analysis that has been done, the authors found four forms of imperative speech in the speech of raja parhata at the traditional Batak Toba party. The form of speech found by the author in the imperative speech of raja parhata at the wedding party of traditional Batak Toba namely the demand imperative speech, the imperative invitation, the ordinary imperative speech, and the imperative speech of the ban. The author not only examines the form of imperative speech raja parhata uses but also examines the imperative courtesy contained in the utterances used raja parhata. The politeness described is maximized, the maxim of wisdom, the maxim of generosity, the maxim of appreciation, the maxim of simplicity, the maxim of consent, and the maxim of sympathy. Of the several types of maxim the authors only find the maxim of wisdom in imperative speech of raja parhata at the wedding party traditional Batak Toba. Key words: language politeness, imperative speech, raja parhata.